2005
DOI: 10.1542/peds.2004-1838
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Bone Mineral Density and Body Composition in Survivors of Childhood Acute Lymphoblastic Leukemia: A 1-Year Prospective Study

Abstract: ABSTRACT. Objectives. Abnormalities in bone mineral density (BMD), body composition, and bone metabolism have been reported in children who were treated for acute lymphoblastic leukemia (ALL) during and after completion of therapy. However, these studies are crosssectional, and no longitudinal data are available in a large group of patients after completion of therapy. In the present study, 1-year longitudinal changes in BMD, body composition, and bone metabolism were evaluated in children with ALL during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 46 publications
(100 reference statements)
5
51
0
1
Order By: Relevance
“…Our findings are consistent with other reports [23][24][25], in that that we noted the most significant impact on bone status in subjects at least 1-year on chemotherapy and within 1-year following completion of therapy. In a longitudinal study of total body aBMD [25], a significantly higher increase in aBMD was observed in survivors of ALL as compared with gender, age, and pubertal stage matched controls, suggesting that there is an improvement in total bone mass with time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with other reports [23][24][25], in that that we noted the most significant impact on bone status in subjects at least 1-year on chemotherapy and within 1-year following completion of therapy. In a longitudinal study of total body aBMD [25], a significantly higher increase in aBMD was observed in survivors of ALL as compared with gender, age, and pubertal stage matched controls, suggesting that there is an improvement in total bone mass with time.…”
Section: Discussionsupporting
confidence: 93%
“…In a longitudinal study of total body aBMD [25], a significantly higher increase in aBMD was observed in survivors of ALL as compared with gender, age, and pubertal stage matched controls, suggesting that there is an improvement in total bone mass with time.…”
Section: Discussionmentioning
confidence: 97%
“…a 25OhD levels are presented as given in the original studies. Median levels were presented by some authors (15,16,18,19), whereas other studies used mean values (9,11,12,14,17). some studies did not present sD values (12,13) or interquartile ranges (19) for 25OhD.…”
Section: Serum 25ohd Levelsmentioning
confidence: 99%
“…These epidemiological and observational findings are supported by clinical trials showing reduced cancer incidence with vitamin D supplementation (7), and by laboratory studies showing that 1,25(OH) 2 D 3 promotes cell differentiation, inhibits proliferation, and exhibits proapoptotic and anti-angiogenic properties (3,8). Despite the wealth of data regarding vitamin D and cancer, only a handful of studies have assessed vitamin D status in pediatric patients with malignancy, and all included relatively small numbers of patients ( Table 1) (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 93%
“…This is notably confirmed by the fact that our controls with normal bone mass had received the same treatment. Others have also looked at bone markers in survivors [19][20][21][22] and have had the same results of no persisting abnormalities of bone mineral metabolism.…”
Section: Discussionmentioning
confidence: 90%